The Effect of Employee Competence and Regulatory Compliance on the Effectiveness of Goods and Services Procurement Through Contract Verification Quality in the Goods and Service Procurement Division of the Deli Serdang Regency Secretariat - Gita Arinsa; Ramadha Yanti Parinduri; Barham Siregar (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This study aims to analyze the influence of employee competence and regulatory compliance on the effectiveness of goods and services procurement, as well as tp determine the mediating role of contract verification quality within the procurement unit of the secretariat of deli Serdang regency. The research employs a quantitative apporch with an explanatory method. The population consists of 16 employees, all of whom were used as the sample trough saturates sampling. Data were collected trough questionnaires, observations, and documentation, and analyzed using multiple linear regression and the sobel test. The results show that employee competence and regulatory compliance have a positive and significant effect on procurement effectiveness. Furthermore, employee competence and regulatory compliance simultaneously have a significant effect on contract verification quality. However, the sobel test results indicate that contract verification quality does not mediate the relationship between employee competence and regulatory compliance on procurement effectiveness. Therefore, procurement effectiveness is influence more direcly by competence and compliance rather than the mediating role of contract verification quality.Keywords: Contract Verification, Effectiveness of Procurement of Goods and Services, Employee Competence, Regulatory Compliance